Alkylimidazolium Ionic Liquids as Antifungal Alternatives: Antibiofilm Activity Against Candida albicans and Underlying Mechanism of Action - Reddy, G. Kiran Kumar; Nancharaiah, Y. V. (Frontiers in Microbiology, 2020)
Candida albicans is an opportunistic pathogen causes fungal infections that range from common skin infections to persistent infections through biofilm formation on tissues, implants and life threatening systemic infections. New antifungal agents or therapeutic methods are desired due to high incidence of infections and emergence of drug-resistant strains. The present study aimed to evaluate (i) the antifungal and antibiofilm activity of 1-alklyl-3-methyl imidazolium ionic liquids ([CnMIM]+[X]-, n=4, 12 and 16) against Candida albicans ATCC 10231 and two clinical C. albicans strains and (ii) the mechanism of action of promising antifungal ionic liquid on C. albicans. Two of the tested compounds were identified as more effective in preventing growth and biofilm formation. These ionic liquid compounds with –dodecyl and –hexadecyl alkyl groups effectively prevented biofilm formation by fluconazole resistant C. albicans 10231 and two other clinical C. albicans strains. Although both the compounds caused viability loss in mature C. albicans biofilms, an ionic liquid with –hexadecyl group ([C16MIM]+[Cl]-) was more effective in dispersing mature biofilms. This promising ionic liquid compound ([C16MIM]+[Cl]-) was chosen for determining the underlying mode of action on C. albicans cells. Light microscopy showed that ionic liquid treatment led to a significant reduction in cell volume and length. Increased cell membrane permeability in the ionic liquid treated C. albicans cells was evident in propidium iodide staining. Leakage of intracellular material was evident in terms of increased absorbance of supernatant and release of potassium and calcium ions into extracellular medium. A decrease in ergosterol content was evident when C. albicans cells were cultured in the presence of antifungal ionic liquid. Dichloro-dihydro-fluorescein diacetate assay revealed reactive oxygen species generation and accumulation in C. albicans cells upon treatment with antifungal ionic liquid. The effect of antifungal ionic liquid on mitochondria was evident by decreased membrane potential (measured by Rhodamine 123 assay) and loss of metabolic activity (measured by MTT assay). This study demonstrated that imidazolium ionic liquid compound exert antifungal and antibiofilm activity by affecting various cellular processes. Thus, imidazolium ionic liquids represent a promising antifungal treatment strategy in lieu of resistance development to common antifungal drugs.